Some problems of legal regulation of the search in Ukraine - Рибікова, Ганна Володимирівна; Грекова, Лілія Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The institution of search in the effective Criminal Procedure Law has been largely developed, as some issues, important for this investigatory (inquiry) operation, were described more in detail, issues such as: grounds for search, the implementation order of investigating judge’s decision concerning the search procedure indicating an exhaustive number of its participants, the obligation to take appropriate measures to ensure the presence of persons whose rights and legitimate interests may be limited or violated, handing of a second copy of the search protocol to the person who was searched, or to an adult member of his/her family or to his/her representative in case of his/her absence and others. For instance, the problem of identifying officials to whom a copy of the search protocol should be handed over during the search of the enterprise, institution or organization, was regulated. However, there are issues that require further research: lack of a legal definition of "search", "personal search", referring of a vehicle search to personal search in some cases, determination of the term within which the investigator or the prosecutor is obliged to apply for a search to the investigating judge in case it was carried out without judgment. The object of this article is to study some of the problems occurring during search and to find ways of their settlement. The article deals with these issues more in detail and is based on foreign experience (Russian Federation, Armenia, Kazakhstan, Republic of Belarus, Poland and France). The author proposes several changes to the current legislation in order to improve legal regulation based on the research of some problems in legal regulation of search procedures.